The school fair - Burgess, Lynne; Parsons, Anne (Heinemann Oxford, 1996)
This pack includes six copies of the title "The School Fair", which supports Stage 6 of the "Storyworlds" guided reading series. The gradual increase in the amount of text aims to help children develop reading skills and improve reading confidence.